The Divergent of Ideational Metafunction Realizations in Novel Graphic Translation - Putri Yuni Utami; M.R Nababan; Riyadi Santosa (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
This article is a translation product oriented study designed to investigate a systemic way of analyzing the divergent of Ideational metafunction realizations in novel graphic translation using Systemic Functional Linguistics (SFL). The objectives of this study are to identify divergent of ideational realizations in the translation and what cause them. The study is a descriptive qualitative with an embedded case study. The linguistics data of this study included all the lingual units of translation namely clauses, phrases and words in the monologue and dialogue of the main character in graphic novel V for Vendetta: Europe After Reign by Alan Moore and David Lloyd. The content analysis is used to determine the divergent of Ideational metafunction meanings in translation by comparing the source texts and target texts. The results show the divergent of Ideational realizations in the translation occur in (1) experiential meaning (transitivity structure and lexical items) (2) logical meaning. The divergences in transitivity structure and lexical items are caused by idiom phrases, politeness strategy, and intertextuality. The logical subtype divert in clauses interdependency which caused by two factors namely (1) the translation not maintaining the structure of the source language by downgrading in clause rank and (2) the limitations of the speech balloon format.